2008
DOI: 10.1373/clinchem.2008.103499
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Adiponectin, Leptin, and Metabolic Correlates of Insulin Resistance: A Longitudinal Study in British Children; 1: Prepuberty (EarlyBird 15)

Abstract: BACKGROUND:The emergence of type 2 diabetes in young populations has mirrored a rising prevalence of obesity and insulin resistance during childhood and adolescence. At the same time, the role of adipokines as links between obesity and insulin resistance is becoming more appreciated. We sought to establish age-and sex-specific distributions of metabolic correlates of insulin resistance in healthy prepubertal children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
2
16
0
3
Order By: Relevance
“…There are some studies in healthy children on the national level, [8][9][10]20 but their comparability with our results is limited mostly because of either a different age distribution of the sample or due to incomparable laboratory analyses. Pre-analytical (for example, serum vs plasma) and analytical factors (laboratory method) can significantly affect measured concentrations of leptin and adiponectin.…”
Section: Leptin and Adiponectin Values For Children E Erhardt Et Almentioning
confidence: 53%
See 2 more Smart Citations
“…There are some studies in healthy children on the national level, [8][9][10]20 but their comparability with our results is limited mostly because of either a different age distribution of the sample or due to incomparable laboratory analyses. Pre-analytical (for example, serum vs plasma) and analytical factors (laboratory method) can significantly affect measured concentrations of leptin and adiponectin.…”
Section: Leptin and Adiponectin Values For Children E Erhardt Et Almentioning
confidence: 53%
“…The development of the hormone levels over age were reported by others previously. Murphy et al 20 showed an age-dependant increase of leptin and a decrease of adiponectin in British children between the ages of 5 and 8 years. A Spanish study 22 examining 789 normal-weight children found that the leptin levels rose from 5 to 15 years of age in parallel with total body weight.…”
Section: Leptin and Adiponectin Values For Children E Erhardt Et Almentioning
confidence: 98%
See 1 more Smart Citation
“…Fasting plasma insulin was higher in girls, even allowing for their BMI and body composition. This might also be explained on the basis of earlier puberty (an insulin-resistant state), or conversely that girls may be intrinsically more insulin resistant (26) . We had expected HDL-cholesterol concentration to be directly related to placental and birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…Between 5 and 8 years of age, metabolic health appears to improve regardless of BMI, with an increase in leptin and a decrease in adiponectin (37). In fact, adiponectin levels in childhood show a marked reversal of the positive body mass correlations observed during the neonatal period: plasma adiponectin levels at age 5 are inversely correlated with percentage of body fat.…”
Section: Childhood and Pubertymentioning
confidence: 95%